Central tendency and variability in biological systems - Lucien J. Cardinal (Greater Baltimore Medical Center, 2015)
In this article, the author reviews the manner in which researchers characterize data. Normality, standard deviation, mean, and other concepts related to parametric statistics are discussed in common language, with a minimum of jargon and with clinical examples.